Compact frequency-reconfigurable slot patch antenna with gain enhancement via metasurface integration - Ahmad, Khalid Subhi; Al Gburi, Ahmed Jamal Abdullah; Abd Aziz, Mohamad Zoinol Abidin (Elsevier GmbH, 2025)
This work presents a frequency-reconfigurable slot antenna (FRSA) design that features a rectangular patch with a longitudinal slot on the ground plane, connected to eight vertical slots for basing. The proposed FRSA includes seven ideal switches (labeled w1–w7) positioned along the longitudinal slot, facilitating its reconfigurable functionality. By toggling these switches ON and OFF, the antenna operates in nine different modes. A single-layer metasurface reflector (MSR) was integrated below the FRSA to enhance the antenna’s gain and directivity. The proposed MSR consists of a 2 × 2 array with a unit cell (UC) size of 18.25 mm× 15.025 mm, optimized to produce a center-operating frequency. The MSR achieves a stopband transmission coefficient (S21) below − 10 dB and exhibits a linear reflection phase within the bandwidth of 3.30 ─ 5.96 GHz, nearly encompasses the FRSA frequency tuning range 3.05 – 5.16 GHz. Combining the FRSA and MSR significantly enhanced performance. The gain improved by 2.49 dB overall, rising from 3.14 dB to 5.63 dB in the lower band and from 5.25 dB to 5.38 dB in the upper band. Varying the FRSA and MSR gap enabled more gain optimization, enabling the gain to range from 3.93 dB to 6.09 dB. The FRSA with MSR covers an operating frequency range of 3.05 GHz to 5.24 GHz and supports operation at 3.05 GHz, 3.38 GHz, 3.98 GHz, 4.06 GHz, 4.34 GHz, 4.70 GHz, 4.74 GHz, 4.80 GHz, and 5.24 GHz. The proposed FRSA with MSR maintains a compact configuration, as the MSR’s size matches the antenna’s dimensions (0.38 λ₀ × 0.31 λ₀). The gap between the MSR and the antenna is only 20 mm (0.204 λ₀), where the wavelength (λ₀) corresponds to the minimum operating frequency of 3.05 GHz in free space. A prototype of the FRSA with MSR was fabricated and its performance was validated through measurements. The proposed antenna is well-suited for applications of S-band, C-band, and cognitive radio technologies.